Increasing bronchiectasis prevalence in Germany, 2009–2017: a population-based cohort study. Issue 6 (5th December 2019) - Ringshausen, Felix C.; Rademacher, Jessica; Pink, Isabell; de Roux, Andrés; Hickstein, Lennart; Ploner, Tina; Welte, Tobias; Diel, Roland
Bronchiectasis is a chronic airway disease with often disabling symptoms, which is associated with excess mortality and a substantial economic burden for healthcare systems [1]. Although considered to be one of the most neglected diseases in respiratory medicine [2], bronchiectasis is apparently more common than previously thought [3, 4]. While trends regarding its epidemiology have been published for the UK and the USA, with marked increases in prevalence rates reported [5–7], such studies are missing for most countries including Germany. However, these basic epidemiological data are needed in order to inform healthcare authorities and policy makers regarding resource allocation and requirements planning. Thus, the objective of the present study was to provide insights into the trends of bronchiectasis prevalence in Germany. Bronchiectasis prevalence in Germany increased on average by 10% per year between 2009 and 2017 http://bit.ly/2P4KcyW